Direct C–H Arylation of Heteroarenes with Aryl Chlorides by Using an Abnormal N‐Heterocyclic‐Carbene–Palladium Catalyst. Issue 5 (8th February 2017) - Ahmed, Jasimuddin; Sau, Samaresh Chandra; P, Sreejyothi; Hota, Pradip Kumar; Vardhanapu, Pavan K.; Vijaykumar, Gonela; Mandal, Swadhin K.
Abstract : Herein, we report a versatile catalytic system for the direct C–H arylation of heteroarenes with activated aryl chloride substrates. The catalyst works successfully for a variety of heteroarenes and aryl chloride coupling partners under very low catalyst‐loading conditions. We have successfully performed the direct C–H arylations of 1‐methylpyrrole, 1‐methylindole, furan, thiophene, furfural, and N ‐benzyl‐1, 2, 3‐triazole with aryl chloride partners in good yields without the use of any additives. Furthermore, we used this catalytic process to develop a one‐pot synthetic protocol for the muscle relaxant dantrolene on a gram scale. Additionally, the present catalytic system can be used to perform consecutive arylations in one pot. Abstract : The C–H functionalization of various heteroarenes with aryl chlorides is catalyzed by a palladium(II) catalyst and is used for an efficient one‐pot synthesis of the muscle relaxant dantrolene.